Patterns and determinants of vegetable intake in Babati District, Tanzania - Jape, V.W. (University of Copenhagen, 2017)
The vegetable has potential to expand the diversity of rural and urban diets thereby improve human nutrition and health. The World Health Organization (WHO) recommends an intake of a minimum of 240 grams of vegetable per person per day in order to supply the body with the required micronutrients that are necessary to improve human health and reduces the risk of developing chronic diseases and disorders such as obesity and malnutrition. Despite the nutritional benefits, consumption levels, particularly in developing countries, are generally reported to be below the recommended level. This study presents the current consumption status and analyses the factors influencing household vegetable intake in Babati District, Tanzania. The study used cross-sectional data from 257 farm households and applied a binary logistic regression model to estimate determinants of vegetable intake. Results show that the mean daily intake of vegetable per person is 205.9 grams. Thirty-two percent of the sampled households had mean daily intake per person below the minimum recommended level. Education level, income, household size, having vegetable home garden, gender of the head and perception of the safety of vegetables sold in the market were found to significantly contribute to the vegetable consumption. The policy implication of the findings is that strategies that encourage households to grow vegetables at home, improve access to education and knowledge about healthy eating and build the capacity of women in making food-related decisions are likely to foster more consumption of vegetables.